Electrical imaging resistivity study at the coastal area of Sungai Besar, Selangor, Malaysia - Baharuddin, M.F.T.; Hashim, Roslan; Taib, S. (2009)
A geophysical method was used in studying the effect of environmental impact and shoreline physical changes on coastal-area salinity of both soil and groundwatcr at the Sungai Besar area in Malaysia. The environmental impact was a previous flooding of the shore by seawater and the consequent severe coastal erosion. 2-D geo-clcctrical resistivity technique was used in evaluating the extent of salinity to soil and to groundwater. Resistivity was measured through an ABEM SAS 1000 C Terrameter. 2-D electrical-imaging resistivity data of subsurface profile for each survey line were calculated through inverse modelling, aided by borehole data, which showed the lithology; Quaternary alluvium sediments more than 80 m deep, composed of alternating layers of sand, silt and clay. From the two resistivity-image profiles obtained, spots of saline plume were found scattered on top of the impermeable-layer marine clay, with less than 0.2 ohm m, resistivity. Resistivity-image profile L, showed saline plume spots to have penetrated the first confined aquifer found at depths of 18.00-34.50 m below ground surface, while resistivity-image profile L> did not show the presence of any such plume. The resistivity-image profiles also revealed that the second confined aquifer of each profile has not been affected by the saltwater contamination. In terms of salinity distance, the L, image profile dominated the full 400 m distance, whereas the L. profile shows the salinity condition lo be about 250 m from shoreline. The results therefore suggest that the salinity of the groundwater aquifer is due probably to ancient seawater-flooding that has long percolated through the sediments, rather than lo direct seawater-intrusion.